The Fabrication of Highly Conducting and Thermo-mechanically Robust Metal Thin Film - Quigley, Shannan Marie (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2025)
Recent research from high-resolution surface probe microscopy and atomic simulation have identified that grain boundaries in [111] F.C.C. thin copper films can restructure in a region immediately below the surface. DFT quantum transport and mean time to failure calculations indicate that the restructured boundaries have improved electric transmission capabilities as well as enhanced resistance to electromigration compared to their [111] counterparts. This thesis aims to produce a thin film sample consisting predominantly of restructured grain boundaries. The starting material for this research was 50 nm copper (111) thin films. These samples were etched to a thickness scale where restructured boundaries could predominate via a two-step acetic acid etch. Etch studies revealed a difference in etch rate and sample roughness post-etch depending on sample grain size. Annealing was added between oxidation-etch rounds to try to minimise sample roughness and allow the emergent grain boundary to be reconstructed. S.T.M. revealed that the etch-damaged boundaries could not be recovered. Likewise, resistivity measurements of copper films at various points of the etch-anneal process could be modelled via a combination of surface scattering and grain boundary scattering models. The change in resistivity as a function of process time was best modelled when the reflectivity parameter for the grain boundaries was allowed to vary for each step of sample processing. The results of the electrical characterisation support the interpretation that the processing employed to thin these samples damages grain boundaries.
APPROVED
Keywords: Grain Boundaries; Atomic Force Microscopy; Etching; Copper; Surface